Is Hinduism ambivalent about suicide?. (August 2018) - Vijayakumar, Lakshmi; John, Sujit
Background: Hinduism is one of the oldest religions in the world and has over 1.1 billion adherents comprising about 16% of the global population living mainly in India and Nepal. The stand of Hinduism on suicide has been ambiguous through the ages, on one hand, condemning general suicides, while condoning religious suicides on the other. This ambiguity is reflected in contemporary India and among the Indian diaspora. Aims: To examine the stand of Hinduism as a religion in the context of suicide. Method: A selected review of literature covering the major Hindu religious texts, cultural practices and suicide. Results: People who follow Hinduism have a suicide rate of about 21 per 100, 000 population compared to the global average of 11.4. Hindu countries have higher rates of suicide compared to Islamic and Christian countries, but these rates are lower when compared to Atheist and Buddhist countries. This is reflected in the Indian diaspora as well with reports from Fiji, the Caribbean, Malaysia and the United Kingdom, indicating that suicide was disproportionately high among those of Indian origin. However, a strong faith in Hinduism acts as protective factor. The Hindu belief in karma fosters a sense of acceptance of the vicissitudes of life with equanimity, and the belief in the cycle of births and deaths renders suicide meaningless, as one's soul continues after death. Their religious beliefs makes the Hindus tolerate and accept hardships and calamities stoically. Conclusion: In certain situations, the Hindu religion acts as a protective factor, whereas at other times, it may increase the risk of suicide. It is important to understand these different nuances in the Hindu religion in formulating a culturally appropriate suicide prevention strategy.